GAN 오버샘플링 기법과 CNN-BLSTM 결합 모델을 이용한 부정맥 분류 - 조익성(Ik-Sung Cho); 권혁숭(Hyeog-Soong Kwon) (한국정보통신학회논문지, 2022)
Arrhythmia is a condition in which the heart has an irregular rhythm or abnormal heart rate, early diagnosis and management is very important because it can cause stroke, cardiac arrest, or even death. In this paper, we propose arrhythmia classification using hybrid combination model of CNN-BLSTM. For this purpose, the QRS features are detected from noise removed signal through pre-processing and a single bit segment was extracted. In this case, the GAN oversampling technique is applied to solve the data imbalance problem. It consisted of CNN layers to extract the patterns of the arrhythmia precisely, used them as the input of the BLSTM. The weights were learned through deep learning and the learning model was evaluated by the validation data. To evaluate the performance of the proposed method, classification accuracy, precision, recall, and F1-score were compared by using the MIT-BIH arrhythmia database. The achieved scores indicate 99.30%, 98.70%, 97.50%, 98.06% in terms of the accuracy, precision, recall, F1 score, respectively. 부정맥이란 심장이 불규칙한 리듬이나 비정상적인 심박동수를 갖는 것을 말하며, 뇌졸중, 심정지 등을 유발하거나 사망에도 이를 수 있는 만큼, 조기 진단과 관리가 무엇보다 중요하다. 본 연구에서는 심전도 신호의 QRS 특징 추출에 적합한 CNN과 기존 LSTM의 직전 패턴의 수렴 한계를 해결할 수 있는 BLSTM을 연결한 CNN-BLSTM 결합 모델을 이용한 부정맥 분류 방법을 제안한다. 이를 위해 먼저 전처리 과정을 통해 잡음을 제거한 심전도 신호에서 QRS 특징점을 검출하고 단일 비트 세그먼트를 추출하였다. 이때 데이터의 불균형 문제를 해결하기 위해 GAN 오버샘플링 기법을 적용하였다. 이 후 합성곱 계층을 통해 부정맥 신호의 패턴을 정밀하게 추출하도록 구성하고 이를 BLSTM의 입력으로 사용한 후 매개변수를 학습시키고 검증 데이터로 학습 모델을 평가한 후 부정맥 분류의 정확도를 확인하였다. 제안한 방법의 우수성을 입증하기 위해 MIT-BIH 부정맥 데이터베이스를 이용하여 분류의 정확도, 정밀도, 재현율, F1-score를 비교하였다. 성능평가 결과 각각 99.30%, 98.70%, 97.50%, 98.06%로 우수한 분류율을 나타내는 것을 확인할 수 있었다.